Electrical stimulation induced pre-vascularization of engineered dental pulp tissue - Ying-tong Wang; Jia-ying Zhou; Kai Chen; Xiao Yu; Zhi-yong Dong; Yu-shan Liu; Xiao-ting Meng (Regenerative Therapy)
Vascularization is a key step to achieve pulp tissue regeneration and in vitro pre-vascularized dental pulp tissue could be applied as a graft substitute for dental pulp tissue repair. In this study, human dental pulp stem cells (DPSCs) and human umbilical vein endothelial cells (hUVECs) were co-cultured in 3D Matrigel and 150 mV/mm electric fields (EFs) were used to promote the construction of pre-vascularized dental pulp tissue. After optimizing co-cultured ratio of two cell types, immunofluorescence staining, and live/dead detection were used to investigate the effect of EFs on cell survival, differentiation and vessel formation in 3D engineered dental pulp tissue. RNA sequencing was used to investigate the potential molecular mechanisms by which EF regulates vessel formation in 3D engineered dental pulp tissue. Here we identified that EF-induced pre-vascularized engineered dental pulp tissue not only had odontoblasts, but also had a rich vascular network, and smooth muscle-like cells appeared around the blood vessels. The GO enrichment analysis showed that these genes were significantly enriched in regulation of angiogenesis, cell migration and motility. The most significant term of the KEGG pathway analysis were NOTCH signaling pathway and Calcium signaling pathway etc. The PPI network revealed that NOTCH1 and IL-6 were central hub genes. Our study indicated that EFs significantly promoted the maturation and stable of blood vessel in 3D engineered pulp tissue and provided an experimental basis for the application of EF in dental pulp angiogenesis and regeneration.